Liposomes as models for membrane integrity. (13th May 2019) - Routledge, Sarah J.; Linney, John A.; Goddard, Alan D.
Abstract : Biological membranes form the boundaries to cells. They are integral to cellular function, retaining the valuable components inside and preventing access of unwanted molecules. Many different classes of molecules demonstrate disruptive properties to the plasma membrane. These include alcohols, detergents and antimicrobial agents. Understanding this disruption and the mechanisms by which it can be mitigated is vital for improved therapeutics as well as enhanced industrial processes where the compounds produced can be toxic to the membrane. This mini-review describes the most common molecules that disrupt cell membranes along with a range of in vitro liposome-based techniques that can be used to monitor and delineate these disruptive processes.